Paving the Way to Personalized Genomic Medicine: Steps to Successful Implementation - Fackler, J. L.; McGuire, A. L. (Current Pharmacogenomics and Personalized Medicine, 2009)
Over the last decade there has been vast interest in and focus on the implementation of personalized genomic medicine. Although there is general agreement that personalized genomic medicine involves utilizing genome technology to assess individual risk and ensure the delivery of the “right treatment for the right patient at the right time,”different categories of stakeholders focus on different aspects of personalized genomic medicine and operationalize it in diverse ways. In order to move toward a clearer, more holistic understanding of the concept, this article begins by identifying and defining three major elements of personalized genomic medicine commonly discussed by stakeholders: molecular medicine, pharmacogenomics, and health information technology. The integration of these three elements has the potential to improve health and reduce health care costs, but it also raises many challenges. This article endeavors to address these challenges by identifying five strategic areas that will require significant investment for the successful integration of personalized genomics into clinical care: (1) health technology assessment; (2) health outcomes research; (3) education (of both health professionals and the public); (4) communication among stakeholders; and (5) the development of best practices and guidelines. While different countries and global regions display marked heterogeneity in funding of health care in the form of public, private, or blended payor systems, previous analyses of personalized genomic medicine and attendant technological innovations have been performed without due attention to this complexity. Hence, this article focuses on personalized genomic medicine in the United States as a model case study wherein a significant portion of health care payors represent private, nongovernment resources. Lessons learned from the present analysis of personalized genomic medicine could usefully inform health care systems in other global regions where payment for personalized genomic medicine will be enabled through private or hybrid public-private funding systems.
Keywords: ethics